THE TAX SYSTEM IN EGYPT IN THE 18th 19th CENTURIES - M. El Sourougi , Prof.Mohamed (مجلة كلية الاداب, 1973)
This papers deals with three distinguished periods: First, the tax system in Ottoman Egypt during the 18th century, second, the tax system during the period of the French expedition (1798-1801), which differs from the previous and seccessive period; and thirdly, the development of the tax system in Egypt during the reign of Mohammad Ali, ie, in the first half of the 19th century. No doubt, the financial and taxation system in closely connected with Ottoman rule and administration in Egypt. The regularity of the financial and taxation condition indicated that Ottoman rule and administration was stable. The mal-administration affected consequently the financial and taxation system where the taxes and the means of collecting them varied considerably. Bribery spread on a great scale, and only few sums of the revenue reached the treasury. The tax collectors misused their authorities and the tax payers were forced to pay many different taxes.